The experiences of high-risk young adults with type 1 diabetes transitioning to real-time continuous glucose monitoring – A thematic analysis - Vicky McKechnie; Parizad Avari; Pei Chia Eng; Rebecca Unsworth; Monika Reddy; Stephanie A. Amiel; Victoria Salem; Shivani Misra (PLoS ONE, 2025)
Background Real-time continuous glucose monitoring (rtCGM) is now the standard care for people with type 1 diabetes. However, whilst its impact on glycaemic outcomes is well-documented, its psychosocial effects, particularly in young adults experiencing extreme hyperglycaemia, remain poorly understood. Objectives We aimed to explore the psychosocial impact of rtCGM on young adults with extreme hyperglycaemia who thus far have not been studied extensively. Research design and methods A qualitative study employing semi-structured interviews was undertaken. Young adults 18–25 years (HbA1c >75mmol/mol (9.0%)), naïve to rtCGM, were provided with rtCGM for 6-months. Interviews (centred on barriers to self-management and experience of rtCGM use) were conducted within 2-weeks of recruitment and at the end. An inductive, thematic analysis of interviews was undertaken. Results Eight participants (median age (IQR) 23.0 (22.0–24.5) years, 100% non-white ethnicity) were recruited with median HbA1c 94 (88–107) mmol/mol [DCCT 10.8 (10.2–12.1)%.]. All participants used multiple daily insulin injections. Despite low rtCGM wear-time (32.2 (23.1–59.4)%), significant improvements were observed in time in range, but no change in HbA1c. Thematic analysis indicated that high levels of disease burden were reported, with rtCGM-related themes identified: 1) interaction with rtCGM data, 2) feelings of control and trust from using rtCGM, and 3) frustration of technology and alarms. Although participants reported that knowledge of glucose levels on their smartphone was convenient and led to ‘greater control’, this was countered by alarm-fatigue, technical difficulties and feeling overwhelmed. Three participants prematurely stopped using rtCGM. Conclusions Young adults with high-risk hyperglycaemia have complex relationships with rtCGM. rtCGM may have benefits in this high-risk group, but are likely to require additional support and must be determined on a case-by-case basis as associated effort may contribute to feelings of distress and/or burnout. Implementing structured educational, psychosocial, and technical support, alongside alternative care models such as more frequent check-ins, should be considered in order to enhance self-management practices with rtCGM and address technology-related challenges.